Cyberculture and Sectarianism in Indonesia: The Rise of Shia Media and Anti-Shia Online Movements - Ida, Rachmah (Jurnal Komunikasi Islam, 2016)
The digital era of information technology appears to be a new space and place for the Indonesian Shiite communities to express their existence and conceal their “cloak” in the country.. Internet, websites, Facebook pages, Blog spots, and Twitter are tilized by these Shiite followers and supporters to show their presence, activities, interactivity, and thoughts about Islam. Responding to those Shia media, the anti-Shia movements such as the fundamentalist Sunnis, the Wahabi-Salafi’s, the Wahabi-Takfiri’s supporters have created their online publications and fan pages to counter those Shia’s publications. The online media battles on sectarianism issue then have sparked in the cyberspace of Indonesia in the last three years.Using a critical cultural studies tradition and textual approach, this study tries to examine the rise of Shia and anti-Shia online media as well as the meanings and contexts in which violent actions occurred amongst the Sunni-Shia Muslim communities on it. This paper also attempts to look closely at the way the media writes, covers, and build opinions and attitude to inform and provoke the public.